Experience With Anti-TNF-α Biologic Agents in Succession in Patients With Crohn's Disease: A Retrospective Analysis of a Single Center. Issue 4 (April 2016) - Ferges, William; Rampertab, Saroja Devi; Shafqet, Muhammad; Salimi, Qasim; You, Geoffrey; Yousefzadeh, Eleazer; Cheng, Jerry Q.; Das, Kiron M.
Abstract : Goals: Our aim was to identify and compare the effectiveness of antitumor necrosis factor biologics when used as initial agents and when used in succession for the treatment of moderate to severe Crohn's disease (CD). Background: Studies directly comparing the efficacy of biologics are lacking. When one biologic loses efficacy, patients are often treated with an alternate biologic. The effectiveness of this strategy has not been thoroughly investigated. Study: This is a retrospective cohort study from a database of 153 patients with CD treated with infliximab, adalimumab, or certolizumab pegol. Response rates determined by physician global assessment were compared between biologics when given as initial agents and after failure of 1 or 2 prior biologics. Results: There were no significant differences in response between infliximab (64.5%), adalimumab (60.0%), and certolizumab pegol (66.7%) when given as initial biologics. As second-line or third-line agents after prior biologic failure, there was a trend toward increased response with infliximab (83.3%) versus adalimumab (52.7%) and certolizumab pegol (59.4%); however, this did not meet statistical significance. After failure or loss of response of 2 previous biologics, use of a third biologic was still effective with a response rate of 54.2%. Conclusions: All 3 biologics have similar efficacy in the treatment of CD when given as initial agents. Infliximab has a trend toward increased response after prior biologic failure; however, this did not meet statistical significance. Even after loss of response or failure of 2 previous biologics, trial of a third alternate biologic is an effective strategy.